GLOBALIZATION AND MANAGEMENT OF PESANTREN: READING THE ASPIRATIONS OF STAKEHOLDERS IN PESANTREN - Rodliyah, St. (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The purpose of this article is to describe the management of pesantren education in responding to various crucial challenges in the era of globalization. Islamic boarding school education occupies an important position in life in the era of globalization, because globalization itself has a positive and negative influence on human life. For this reason, pesantren education must be managed professionally so that its existence continues to progress and develop. The data of this article were obtained through in-depth interviews, passive participation observations, and document studies. Data analysis using qualitative descriptive with Milles Huberman and Saldana's interactive model with steps namely: data collection, data condensation, data presentation, and conclusions. While the validity of the data uses source triangulation and method trianggulation. The results showed that (1) Globalization can be an opportunity and challenge for students at the Al Islah Bondowoso Islamic boarding school, (2) The existence and urgency of pesantren education management in the era of globalization for the community in the Al Islah Bondowoso Islamic boarding school environment is very necessary and must continue to be developed, so that the pesantren is able to meet the demands and needs of the community, (3) The aspirations of Al Islah Bondowoso Islamic boarding school stakeholders towards globalization, hope that pesantren education management is able to respond to globalization wisely and wisely, (4) The programs offered by the Al Islah Bondowoso Islamic boarding school in responding to globalization are by developing formal and non-formal education, language institutions, skills programs, and interpreneursif programs.